A STUDY ON HIGHER SECONDARY STUDENTS EMOTIONAL MATURITY AND ACHIEVEMENT IN ECONOMICS IN TIRUNELVELI DISTRICT (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2012)
The aim of this study is to find out the Emotional Maturity and Achievement in Economics of higher secondary students in Tirunelveli District. 1060 Higher secondary students were taken as sample. The tool used to find out the Emotional Maturity is constructed and standardized by Emotional Maturity Scale Constructed and Validated by K.M.Roma Pal (1984). The Academic achievement in Economics was found out using the tool constructed by the investigator. The mean value of Emotional Maturity scores (136.53) indicates that the higher secondary students are having extremely unstable Emotional Maturity, The mean value of Achievement in Economics scores (M=75.47) indicates that the higher secondary students are having high Achievement in Economics. There is significant difference between male and female, Day scholar and Hostel staying Higher Secondary students with respect to their Emotional Maturity. There is no significant difference between rural and urban, Government and Aided Higher Secondary school students with respect to their Emotional Maturity. There is significant difference between male and female Higher Secondary students with respect to their Achievement in Economics. There is no significant difference between rural and urban, Day scholar and Hostel staying, Government and Aided Higher Secondary school students with respect to their Achievement in Economics.